2019
DOI: 10.1016/j.jid.2019.03.161
|View full text |Cite
|
Sign up to set email alerts
|

085 Autoantigen screening in C3H/HeJ mouse model of alopecia areata revealed high antigenicity of melanocyte-associated antigen epitopes

Abstract: Alopecia areata (AA) is an autoimmune form of hair loss involving infiltration of CD8+ T cells in the hair follicles (HFs) in conjunction with the upregulated antigen presentation processes. The growing (anagen) HFs are preferentially attacked in AA, leading to the hypothesis that epitopes derived from anagen-specific proteins are targeted by the T cells. Melanogenesis is a highly active process during anagen and clinical observations reported preferential loss of pigmented hairs during the initial onset of AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…GOLGA8M, which encodes Golgin A8 family member M, contributes to the development of HBV-related HCC (Jiang et al 2020 ). The researchers have shown that the transport protein SLC24A5 induces a significantly higher frequency of CD8 T cell activation in an autoimmune disease like Alopecia areata (Wang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…GOLGA8M, which encodes Golgin A8 family member M, contributes to the development of HBV-related HCC (Jiang et al 2020 ). The researchers have shown that the transport protein SLC24A5 induces a significantly higher frequency of CD8 T cell activation in an autoimmune disease like Alopecia areata (Wang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%